Inhaltskomische Zungenbrecher als kulturbedingtes Unterhaltungsmittel - Zubach, Oksana A. (Київський національний лінгвістичний університет, 2024)
The article is devoted to the study of German tongue twisters as special representatives of humor and laughing culture in the German-language comic space. The goal is aimed at the study of the lingual and cultural aspects of German tongue twisters in order to reflect their humorous and national cultural potential. Taking into account different approaches to the study of humor, laughter culture and comic speech, the structural and semantic and pragmatic means used in German tongue twisters to express a comic effect and positive emotions are determined, the specificity of the formation of German humor through tongue twisters are revealed, the structural and semantic elements of German tongue twisters are analyzed, which represent the laughing culture of the German-speaking world. Tongue twister are defined as funny short stories, confusing strange sayings, nonsense texts, etc., which predict the formation of a comic effect through their plan of content and plan of expression. In plan of content of tongue twisters, a humorous game is embedded, which causes emotional and expressive tension and turns communication into an informal one. The plan of expression contains elements that pragmatize the comic effect (parallelism, repetition, alliteration, etc.). It is noteworthy that to enhance the comic effect, modified phraseological units, which are identifiers of the cognitive activity of people of the target language culture, are involved in tongue twisters. Tongue twister require adequate vocal representation of text elements, provoke positive emotional reactions and cause laughter. Their structure visualizes national and cultural elements that belong to the background knowledge of the target language culture. When uttering tongue twisters with a certain rhythm, unintentional slurs appear, which also enhances the comic effect. The national and cultural specificity of tongue twisters is revealed through designations of nationalities, proper names, national dishes and drinks, and professions
Keywords: скоромовка; гумор; німецька мова; комічні елементи; гумористична компетентність; 811.112.2:398.9(=112.2)